THE ROLES OF PERCEIVED HIV RISK AND SOCIAL SUPPORT IN WILLINGNESS TO USE PRE EXPOSURE PROPHYLAXIS AMONG PASTORAL YOUTH OF SOUTHERN ETHIOPIA. - Hebo, Sultan Hussen; Spigt, Mark; Schneider, Francine (Ethiopian Journal of Reproductive Health, 2025)
BACKGROUND: Pastoralist youth experience a high HIV vulnerability yet have limited access to prevention services. Pre exposure prophylaxis (PrEP) could close this gap, but little is known about factors of PrEP willingness among pastoralist youth. OBJECTIVE: To examine whether (i) empirically derived HIV risk status predicts willingness to use PrEP, (ii) perceived HIV risk mediates this association, and (iii) social support moderates the pathway from perceived risk to willingness among pastoral youth. METHODS: A population based cross sectional survey was conducted among 638 randomly selected pastoralist youth (15–24 years) in Southern Ethiopia (April–May 2024). HIV risk status was derived with a 3 class latent class analysis of nine behavioral and structural HIV risk indicators. Perceived risk (mediator), social support (moderator) and PrEP willingness were measured by interviewer administered questionnaire. PROCESS macro v4.2 in SPSS tested mediation (Model4) and moderated mediation (Model15) with 5000 bias corrected bootstrap samples, controlling for age and sex. RESULTS: Overall, 40.4% of participants were definitely willing to use PrEP. High risk youth were more willing than low risk peers (adjusted =0.92, p<0.001). Perceived HIV risk partially mediated this link (indirect =0.20, 95 CI0.10–0.35). Social support significantly intensified the effect of perceived risk on willingness (index of moderated mediation=0.21, 95 CI0.03–0.43): among youth with high social support the mediated effect increased relative to those with low support. CONCLUSION: Accurate self assessment of HIV risk is limited among pastoral youth, yet when risk is acknowledged, supportive social networks amplify motivation to use PrEP. Interventions should pair risk communication strategies with social support to enhance PrEP uptake.